OPTIMASI TEKNO-EKONOMI PENGEMBANGAN SISTEM PEMBANGKIT HIBRID EKSISTING MENGGUNAKAN MULTI TOOLS (STUDI KASUS: PULAU SEBIRA) - Adi, Hari Purnomo; Zainal Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia’s pledge to reach Net Zero Emissions (NZE) by 2060 has heightened the urgency to decarbonize diesel‑reliant microgrids in remote islands, where logistics inflate fuel costs and reliability risks. Sebira Island—Jakarta’s northernmost inhabited island—already operates a PV–battery–diesel hybrid system. Building on 2024 field measurements of load and solar resources, this study models the existing assets in PVsyst to obtain high‑fidelity PV energy profiles, then performs techno‑economic optimization with HOMER Pro. We evaluate three scenarios: (i) the current system, (ii) cost‑optimal expansion, and (iii) 100% renewable fraction. The optimal configuration adds 158.4 kWp ground‑mounted PV, 211.2 kWp floating PV, and 1,324 kWh Li‑ion storage, lowering the Levelized Cost of Energy (LCOE) to Rp 4,879.36/kWh (−20% versus the existing system), cutting annual diesel use by ≈141 kL, and reducing CO₂ emissions by ≈372 t/year while fully meeting demand (833,872 kWh/year). Achieving 100% renewable fraction is technically feasible but requires 1,425.6 kWp new PV and 5,875 kWh Li‑ion storage, raising LCOE to Rp 10,938.06/kWh. The results of this study emphasize the importance of modeling for hybrid power plant development to achieve the lowest LCOE and provide practical guidance for clean energy development on small islands. Policy implications highlight the role of floating PV when land is limited for developing existing hybrid systems.